Evaluating the Efficacy of Garlic and Cranberry Extracts against E. coli causing Urinary Tract Infections - Khosravi, Zahra (Biology, Engineering, Medicine and Science Reports)
Background: Escherichia coli (E. coli) is the major cause of community-based Urinary tract infections (UTI). Products from nature have been used in traditional medicine practice although with limited scientific validity. In this study garlic and cranberry extracts was assessed for its efficacy to inhibit E. coli growth. Materials and Methods: Crude garlic and cranberry extracts were obtained and E. coli was isolated from an infected urine sample. Two-fold serial dilution was carried out on the E. coli and crude extract inoculations. Incubation and plating was carried out for 24 hr at 30°C. Colony count was done using a digital Quebec Colony Counter. Results: A general trend of reducing number of average CFU with increasing concentration of both extracts was observed. Garlic was observed to be more potent than the cranberry extract even at the lowest concentration. Conclusion: This study establishes the merit of using garlic and cranberry extract as a household remedy for UTI caused by E. coli.
Keywords: Urinary tract infections; Garlic extract; Cranberry extract; E. coli; Antibiotic resistance; Prophylactic treatment